Estimation of Serum TLR-9,TNF-α, and IL-6 Levels in the Iraqi Patients Diagnosed as Acute Myelogenous Leukemia (Baghdad Science Journal, 2024)
Acute myelogenous leukemia (AML) is a varied group of biological and clinical diseases. It is distinguished by the fast proliferation of aberrant cells in the bone marrow, which interferes with normal blood cell formation. Several studies demonstrated that cytokines released by leukemic cells in an autocrine or paracrine manner influence the proliferation of AML cells. Our study aimed to assess serum levels of TLR-9, TNF-α and, IL-6 in patients of AML. The study was done via the ELISA Technique. The results show a highly significant difference in all parameters in Patients and control. The correlation between immunological parameters using the Pearson correlation coefficient for patients showed that there is a weak correlation between TLR-9 and TNF- α, IL-6 with P-values of 0.47 and 0.23 respectively. This may indicate the complex environment of inflammation. However, there was a strong correlation between TNF- α and IL-6 with a P-value (0.001). This indicates that the secretion of these cytokines was high in patients. All immunological parameters of patients were evaluated using the receiver operating characteristic (ROC) curve to demonstrate that any one of them is a useful tool for identifying and tracking inflammation. The ROC curve's findings revealed that all parameters have good sensitivity and specificity for detecting inflammation and disease activity in AML patients. According to the current study, AML was related to higher levels of TLR-9, TNF-α, and, IL-6 may be affected the prognosis of the disease, increase the risk of the disease progression, and may be used as a biomarker to target AML cells.